1997
DOI: 10.1042/bj3260369
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide reversibly inhibits the epidermal growth factor receptor tyrosine kinase

Abstract: Although it has been demonstrated that NO inhibits the proliferation of different cell types, the mechanisms of its anti-mitotic action are not well understood. In this work we have studied the possible interaction of NO with the epidermal growth factor receptor (EGFR), using transfected fibroblasts which overexpress the human EGFR. The NO donors S-nitroso-N-acetylpenicillamine (SNAP), 1,1-diethyl-2-hydroxy-2-nitrosohydrazine (DEA-NO) and N-{4-[1-(3-aminopropyl)-2-hydroxy-2-nitrosohydrazino]butyl}propane -1, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 48 publications
(66 reference statements)
4
67
1
Order By: Relevance
“…Because in vitro studies demonstrate that NO is primarily a direct cytostatic agent in many cell types including neuroblasts (Garg and Hassid, 1990; Peunova and Enikolopov, 1995; Estrada et al, 1997;Sciorati et al, 1997;Nakaya et al, 2000;Murillo-Carretero et al, 2002), general increases in cerebral NO concentration, such as those derived from NO donor injections or iNOS induction, may promote neurogenesis by indirect mechanisms. In this sense, it is interesting that after stroke, NO stimulates the secretion of vascular endothelial growth factor (Zhang et al, 2003), which has been shown to induce neurogenesis both in vivo and in vitro (Jin et al, 2002).…”
Section: Endogenous No Inhibited Cell Proliferation and Did Not Affecmentioning
confidence: 99%
See 3 more Smart Citations
“…Because in vitro studies demonstrate that NO is primarily a direct cytostatic agent in many cell types including neuroblasts (Garg and Hassid, 1990; Peunova and Enikolopov, 1995; Estrada et al, 1997;Sciorati et al, 1997;Nakaya et al, 2000;Murillo-Carretero et al, 2002), general increases in cerebral NO concentration, such as those derived from NO donor injections or iNOS induction, may promote neurogenesis by indirect mechanisms. In this sense, it is interesting that after stroke, NO stimulates the secretion of vascular endothelial growth factor (Zhang et al, 2003), which has been shown to induce neurogenesis both in vivo and in vitro (Jin et al, 2002).…”
Section: Endogenous No Inhibited Cell Proliferation and Did Not Affecmentioning
confidence: 99%
“…A variety of molecules are involved in the antiproliferative action of NO in different cell types (Lepoivre et al, 1994;Estrada et al, 1997;Sciorati et al, 1997;Nakaya et al, 2000). Among them, EGFR is a good candidate to be mediating the NO effects in the SVZ.…”
Section: Phenotypic Characteristics Of No-sensitive Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other proven or likely targets for nitrosylation in the NF-B pathway include the epidermal growth factor and src tyrosine kinases (24,25), which activate NF-B through p21 ras ; tyrosine phosphatases (26); and NADPH oxidase (27), known to activate NF-B through IKK (presumably by means of the oxidative inactivation of phosphatase). Given the multiple loci of S-nitrosylation in NF-Brelated pathways, the effects of S-nitrosylation may be considered analogous to those of phosphorylation, with a large number of regulatory permutations that combine ultimately to optimize cellular responses.…”
Section: Multifaceted Regulation Of Nf-b By S-nitrosylationmentioning
confidence: 99%